Application of Plant-Growth-Promoting Fungi Trichoderma longibrachiatum T6 Enhances Tolerance of Wheat to Salt Stress through Improvement of Antioxidative Defense System and Gene Expression - Zhang, Shuwu; Gan, Yantai; Xu, Bingliang (Frontiers in Plant Science, 2016)
Soil salinity is a serious problem worldwide that reduces agricultural productivity. Trichoderma longibrachiatum T6 (T6) has been shown to promote wheat growth and induce plant resistance to parasitic nematodes, but whether the plant-growth-promoting fungi T6 can enhance plant tolerance to salt stress is unknown. Here we determined the effect of plant-growth-promoting fungi T6 on wheat seedlings’ growth and development under salt stress, and investigated the role of T6 in inducing the resistance to NaCl stress at physiological, biochemical, and molecular levels. Wheat seedlings were inoculated with the strain of T6 and then compared with non-inoculated controls. Shoot height, root length, and shoot and root weights were measured on 15 days old wheat seedlings grown either under 150 mM NaCl or in a controlled setting without any NaCl. A number of colonies were re-isolated from the roots of wheat seedlings under salt stress. The relative water content in the leaves and roots, chlorophyll content, and root activity were significantly increased, and the accumulation of proline content in leaves was markedly accelerated with the plant growth parameters, but the content of leaf malondialdehyde (MDA) under saline condition was significantly decreased. The antioxidant enzymes-superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) in wheat seedlings were increased by 29%, 39% and 19%, respectively, with the application of the strain of T6 under salt stress; the relative expression of SOD, POD and CAT genes in these wheat seedlings were significantly up-regulated. Our results indicated that the strain of T6 ameliorated the adverse effects significantly, protecting the seedlings from salt stress during their growth period. The possible mechanisms by which T6 suppresses the negative effect of NaCl stress on wheat seedling growth may be due to the improvement of the antioxidative defense system and gene expression in the stressed wheat plants.